Extraction of natural dyes from locust beans and tamarind fruits pods and their fastness properties of colorant on cotton and silk fabrics - Ibrahim Abdullahi Umar (2013)
Locust beans (Parkiabiglobosa/Filicoidea) and Tamarind (Tamarindusindica) are trees grown in most tropical region. They are multipurpose trees with fruits that play a vital role most especially in preparing food delicacy, drinks and commercial purpose as well as for medical values. The fruits pods of locust beans and tamarind trees are normally discarded after opening to remove the seeds, powder and the pasty parts of the fruits for use. The pods when soaked in water releases brownish/pinkish colour which is harmful to aquatic life. The synthetic dyes/colours also poses a threats to human life, pollutes our environment The synthetic dyes/colorant poses a threats to human life, pollutes our environment and this coupled with Nigerian problems of scarcity of dyes, cost of importation, environmental pollution and unemployment opportunities. Therefore, the international community called for urgent attention, urging nations to go back to the re- used of natural dyes to served as an alternatives to this menaced. In order to find a lasting solution to environmental pollution caused by the discarded pods and also create alternative to the harmful synthetic dyes; this study researches on the potential of using the brownish/pinkish colour released by the pods as textile dyes.